2021
DOI: 10.1186/s12986-021-00540-9
|View full text |Cite
|
Sign up to set email alerts
|

Ferulic acid alleviates lipotoxicity-induced hepatocellular death through the SIRT1-regulated autophagy pathway and independently of AMPK and Akt in AML-12 hepatocytes

Abstract: Background Lipotoxicity-induced cell death plays a detrimental role in the pathogenesis of metabolic diseases. Ferulic acid, widespread in plant-based food, is a radical scavenger with multiple bioactivities. However, the benefits of ferulic acid against hepatic lipotoxicity are largely unclear. Here, we investigated the protective effect of ferulic acid against palmitate-induced lipotoxicity and clarified its potential mechanisms in AML-12 hepatocytes. Methods … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 75 publications
(96 reference statements)
0
18
0
Order By: Relevance
“…FA can reduce apoptosis through increasing the ratio of Bcl-2/Bax [ 30 ]. Furthermore, a recent study indicates that FA shows significant protective effects during cellular or tissue damage [ 31 ]. However, the information of the clinical effects of FA supplementation in LPS-induced hepatic injury chickens is limited.…”
Section: Introductionmentioning
confidence: 99%
“…FA can reduce apoptosis through increasing the ratio of Bcl-2/Bax [ 30 ]. Furthermore, a recent study indicates that FA shows significant protective effects during cellular or tissue damage [ 31 ]. However, the information of the clinical effects of FA supplementation in LPS-induced hepatic injury chickens is limited.…”
Section: Introductionmentioning
confidence: 99%
“…Ferulic acid has shown remarkable anti-inflammatory and antioxidant activity in pre-clinical studies and, as sodium ferulate, is widely used in cardiovascular medicine in China [90,91]. Recent studies have found that this may reflect, in large part, the ability of ferulic acid to up-regulate SIRT1 expression at the mRNA and protein level [92][93][94][95][96][97]. This effect has been demonstrated in a number of cell types, and hence appears to be a general effect; its mechanistic basis remains unclear.…”
Section: Manifold Nutraceutical and Dietary Options For Activation Of...mentioning
confidence: 99%
“…Moreover, the oral administration of ferulic acid to rats fed with a high-fat diet alleviated development of non-alcoholic fatty liver disease (NAFLD) by reducing the deposition of triglycerides and cholesterol in the liver [ 37 ]. The compound protects AML-12 hepatocytes against palmitate-induced lipotoxicity by reducing ROS (reactive oxygen species) accumulation and decreasing activation of proinflammatory cytokines, i.e., IL-6 and IL-1β [ 38 ]. Therefore, the development of new forms of functional foods enriched with ferulic acid is reasonable in the case of metabolic diseases.…”
Section: Main Pharmacological Properties Of Famentioning
confidence: 99%